Toxic action of aqueous wheat straw extract on horse e purslane - Khaliq,A. (2012)
The toxic action of aqueous wheat (Triticum aestivum) straw extracts was investigated on germination, early seedling growth, some biochemical attributes and the antioxidant enzymes of horse purslane (Trianthemaportulacastrum). Aqueous extracts of wheat straw were prepared by soaking the wheat straw in distilled water in 1:10 w/v ratio and diluted to obtain the concentrations of 0, 25, 50, 75 and 100%. These were used as pre and post emergence in laboratory and screen house trials. Wheat aqueous extracts exhibited phytotoxicity to horse purslane by inhibiting and delaying its germination and suppressing seedling growth. Wheat phytotoxins in its aqueous extracts suppressed the chlorophyll content and soluble protein, and enhanced soluble phenolics and the activity of antioxidant enzymes as catalase, peroxidase and superoxide dismutase in the seedlings of horse purslane compared with the control. Such inhibitory activity is believed to originate from exposure to wheat phytotoxins that are present in its aqueous straw extract. The suppressive effects of wheat straw need to be investigated further under field conditions.